Prevalence of and factors associated with regular khat chewing among university students in Ethiopia - Astatkie A; Demissie M; Berhane Y; Worku A (Dove Medical Press, 2015)
Ayalew Astatkie,1 Meaza Demissie,2 Yemane Berhane,2 Alemayehu Worku2,3 1School of Public and Environmental Health, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 2Addis Continental Institute of Public Health, Addis Ababa, Ethiopia; 3School of Public Health, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia Purpose: Khat (Catha edulis) is commonly chewed for its psychostimulant and euphorigenic effects in Africa and the Arabian Peninsula. Students use it to help them study for long hours especially during the period of examination. However, how regularly khat is chewed among university students and its associated factors are not well documented. In this article we report on the prevalence of and factors associated with regular khat chewing among university students in Ethiopia. Methods: We did a cross-sectional study from May 20, 2014 to June 23, 2014 on a sample of 1,255 regular students recruited from all campuses of Hawassa University, southern Ethiopia. The data were collected using self-administered questionnaires. We analyzed the data to identify factors associated with current regular khat chewing using complex sample adjusted logistic regression analysis. Results: The prevalence of current regular khat chewing was 10.5% (95% confidence interval [CI]: 6.1%–14.9%). After controlling for sex, religion, year of study, having a father who chews khat, cigarette smoking and alcohol drinking in the adjusted logistic regression model, living off-campus in rented houses as compared to living in the university dormitory (adjusted odds ratio [95% CI] =8.09 [1.56–42.01]), and having friends who chew khat (adjusted odds ratio [95% CI] =4.62 [1.98–10.74]) were found to significantly increase the odds of current regular khat use. Conclusion: Students living outside the university campus in rented houses compared to those living in dormitory and those with khat chewing peers are more likely to use khat. A multipronged prevention approach involving students, the university officials, the surrounding community, and regulatory bodies is required. Keywords: current regular khat chewing, peer pressure, living arrangement, university students